PEMANENAN AIR HUJAN UNTUK KONSERVASI AIR TANAH MELALUI SUMUR RESAPAN (Studi Kasus Perumahan di Daerah Hibrida I, II, dan IV Kota Bengkulu) - Nanda Pratama; Agustin Gunawan; Besperi Besperi (Universitas Bengkulu, 2019)
Residential development at the present grows greater towards the horizontal, as a result of these developments is a change of land-use layout. One of the impacts of land use change order is the occurrence of surface flow (surface run-off), the other impact is the decline in the amount of water recharge into the soil causing ground water table to drop. In response to existing problems, there should be specific conservation techniques. Recharge well is one of the alternatives to minimize the surface flow and ground water conservation. The purpose of this study was to find out how to plan for the conservation of ground water by recharge wells using Sunjoto formula to calculate the debit and dimesion of the well. The resident area of Hibrida I, II, and IV is the place of research, the research activities itself is carried out by the method of interviews and experimenting the absorbtion at the research location. Based on the data and analysis results using the Sunjoto formula, note that the location Hibrida I, II, and IV are planned using the recharge well of circle type with a diameter 0,5 meter and depth1 meter for the recharge well type of individual, and with a diameter 1 meter and depth 1,5 meterfor therecharge well type of communal. Based on the review of total area of the house and yard for recharge well type of communal is planned 21 units with a discharge that can be accommodated in area Hibrida I as much as 0,120 m 3 /s, Hibrida II0,188 m 3 /s, and Hibrida IV 0,335 m 3 /s. Based on a review roof total area of the house the type ofcommunal recharge well planned is 35 units with a discharge that can be accommodated in the area of Hibrida I as much as 0,216 m 3 /s, Hibrida II 0,335 m 3 /s, and Hibrida IV 0,525 m 3 /s